(untitled) - Peerenboom, R. P. (Cambridge, UK,New York, 2002)
China has enjoyed considerable economic growth recently, in spite of a problematic legal system. Randall Peerenboom asserts that China is in transition from rule by law to a version of rule of law, although not a "liberal democratic" version. In addition to scholars and students, this book is of interest to business professionals, policy advisors, and governmental and non-governmental agencies
Keywords: Rule of law,Law reform,Luật pháp Trung Quốc,Cải cách luật pháp; China,China,Trung Quốc